2018
DOI: 10.24297/ijct.v17i2.7754
|View full text |Cite
|
Sign up to set email alerts
|

Gearing Up Education Towards Industry 4.0

Abstract: Industry has changed creatively with manufacturing systems and technological applications supplementing in the work preparation, reporting variants, methods and resources for effective production management by constant improvements and usage has matured it way to Industry 4.0. Industry has undergone various revolutions up to now, and through cyber-physical systems would communicate, collaborate in real time of the process and product value stream. Technology upgrades will bring optimization in various resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 1 publication
0
15
0
1
Order By: Relevance
“…The learning or the realization of the different concepts of Industry 4.0 both theoretically and practically at the university would enormously help its application at the industrial level. It suggests that the universities and educational institutes should deliver courses and trainings to cope with the varied requirements of the new trends of Industry 4.0 [21]. The young talents should be nurtured and exposed to the various aspects of smart technology at the earliest so that they are well-equipped and prepared for the existent industrial revolution [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The learning or the realization of the different concepts of Industry 4.0 both theoretically and practically at the university would enormously help its application at the industrial level. It suggests that the universities and educational institutes should deliver courses and trainings to cope with the varied requirements of the new trends of Industry 4.0 [21]. The young talents should be nurtured and exposed to the various aspects of smart technology at the earliest so that they are well-equipped and prepared for the existent industrial revolution [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that many authors have studied subject matter-based educational needs and relevant ICT infrastructures from the viewpoint of new-generation manufacturing [25,46,[57][58][59][60]. Some authors have emphasized a particular type of knowledge structure and its transformation [61] for the sake of active learning and teaching.…”
Section: Concept Map Creation and Analysismentioning
confidence: 99%
“…In fact, it has been identified that employers demand students with problem-solving skills. In this regard, students need to understand how to deal with such variety of technology from an innovative and critical thinking approach, thus, being required specific academic methods to teach students from a holistic thinking point of view [13].…”
Section: Engineering Education 40mentioning
confidence: 99%